Techniques for Natural Gas Physical Properties Definition for Flow Rate and Volume Metering Systems - Fedir Matiko; Halyna Matiko; Vitalii Roman; Ivan Stasiuk (Energy Engineering and Control Systems)
The results of researching the techniques for natural gas properties determination for flow rate and volume metering systems are presented in the paper. The necessity of developing techniques for calculating the isentropic exponent of natural gas for pressure up to 25 MPa based on a simplified set of parameters of gas composition is shown. New techniques are proposed to define isentropic exponent and dynamic viscosity based on designed analytical dependence for the calculation the pseudo-critical density of natural gas, regression equation for isentropic exponent and improved equation of Dean and Steal for calculating gas dynamic viscosity for high pressure. Techniques adequacy verification is carried out relative to the arrays of calculated values of adiabatic index and viscosity obtained from high-precise equations of gas state and relative to the experimental data of viscosity and sound speed in natural gas. The techniques errors and the range of their application are defined using the verification results.